Pasteurella multocida septic shock in an immunocompromised host - Margarida Martins Mouro; Ana S. Pereira; Rúben Carvalho; Maria Manuel Xavier (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Pasteurella multocida is the most common cause of soft tissue infection in humans following bites caused by dogs and (particularly) cats. Transmission may also occur after scratches inflicted by these animals. The authors present the case of a 78-year-old immunocompromised male who presented to the emergency department with fever and inflammatory signs on his right hand following a cat scratch. He was started on empirical intravenous antibiotics which, after isolation of Pasteurella spp. on a swab sample, was subsequently directed. A total of 3 weeks of antibiotics were administered, the patient improved and was discharged. Ten days after he returned to the hospital with septic shock secondary to recurrence of the cellulitis, and Pasteurella multocida was identified on blood cultures. After availability of the antibiotic sensitivity test, 6 weeks of levofloxacin and penicillin were administered. The patient recovered, despite being immunocompromised and Pasteurella spp. bacteremia having a relevant mortality rate.